IDIOM PADA RUBRIK OPINI HARIAN RIAU POS - Febita Aisyah; Dudung Burhanudin; Hermandra Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThis study was entitled ”Idioms in Opinion Heading of Riau Pos Daily Newspaper”. It discussed about (1) What are the categories of idiom which were contained in the opinion heading of Riau Pos in edition of July, 2013?, and (2) What are the idiomatic meanings which were contained in the opinion heading of Riau Pos in edition of July, 2013?. The objective of this study was to describe (1) the categories of idiom which were contained in the opinion heading of Riau Pos in edition of July, 2013, (2) the idiomatic meanings which were contained in the opinion heading of Riau Pos in edition of July, 2013. This study used descriptive method. The data were language corpus in the opinion heading of Riau Pos in edition of July, 2013 which contained some idioms. The data source was the discourses in the opinion heading of Riau Pos in edition of July, 2013. The data collection was conducted by using documentation technique. The results of this study found 54 idioms. There were three categories of in the opinion heading of Riau Pos in edition of July, 2013. They were (1) 39 idioms of nominal phrase, (2) 12 idioms of verbal phrase, and (3) 3 idioms of adjective phrase. In term of idiomatic meanings, there were 25 idioms having complete meanings and 29 idioms having partial meanings.  Key words: Idioms and Opinion